Hypersonic aerodynamic interference investigation for a two-stage-to-orbit model. (March 2020) - Jia, Juhong; Fu, Debin; He, Zepeng; Yang, Junfan; Hu, Lijie
Abstract: To investigate the aerodynamic interference challenges for hypersonic vehicles, a new type of conceptual TSTO model is considered, which consists of a trapezoid wing as the booster and a hemisphere-cone-cylinder wing as the orbiter. Based on the three-dimensional hybrid LES/RANS numerical simulation method, the mechanism of high surface heat flux and the effect of stage separation between booster and aircraft in hypersonic flight are studied in detail. The results show that the oblique shock generated by the booster impinges on the bow shock in a three-dimensional region around the orbiter nose. Obviously, this interaction brings about a steep temperature gradient and high peak values of pressure and heat flux. When the bow shock under the orbiter is incident to the upper surface of the booster, it will trigger a shock-wave/boundary-layer interaction, which gives rise to the peak pressure and heat flux. When the reflected bow shock impacts the lower surface of the orbiter, it will initiate another interaction. When the two stages separate from each other, the increase in the normal distance between two stages results in a decrease in pressure and heat flux. When the vertical distance is large enough, the reflected bow shock impinges on the rear of the orbiter without producing an interaction. At that moment, the pressure and heat flux maintain low values. Highlights: Hypersonic aerodynamic interaction of a TSTO model is investigated. The incidents of bow shock brings about the shock wave boundary layer interaction. The increasing of stages distance results in decreased pressure and heat flux.